The Importance of Compensation, Supervision, and Transformational Leadership on the Affective Commitment of Employee Work at the Yogyakarta Industry and Trade Office - Devi Keni Yampap; Pryaekti Pryaekti (Jurnal Ilmu Manajemen Profitability, 2022)
The purpose of this study was to determine the effect of compensation, supervision, and transformational leadership on the work affective commitment of employees at the Yogyakarta Industry and Trade Office. The type of research in this research is descriptive quantitative. The population is all employees at the Yogyakarta Industry and Trade Office, with a sample of 56 respondents. The results of this study indicate that compensation, supervision, and transformational leadership have a positive influence either partially or simultaneously on affective commitment